Macrophages Mediate a Switch between Canonical and Non-Canonical Wnt Pathways in Canine Mammary Tumors - Król, Magdalena; Mucha, Joanna; Majchrzak, Kinga; Homa, Agata; Bulkowska, Małgorzata; Majewska, Alicja; Gajewska, Małgorzata; Pietrzak, Marta; Perszko, Mikołaj; Romanowska, Karolina; Pawłowski, Karol; Manuali, Elisabetta; et al. (PloS one, 2014)
According to the current hypothesis, tumor-associated macrophages (TAMs) are "corrupted" by cancer cells and subsequently facilitate, rather than inhibit, tumor metastasis. Because the molecular mechanisms of cancer cell-TAM interactions are complicated and controversial we aimed to better define this phenomenon. Using microRNA microarrays, Real-time qPCR and Western blot we showed that co-culture of canine mammary tumor cells with TAMs or treatment with macrophage-conditioned medium inhibited the canonical Wnt pathway and activated the non-canonical Wnt pathway in tumor cells. We also showed that co-culture of TAMs with tumor cells increased expression of canonical Wnt inhibitors in TAMs. Subsequently, we demonstrated macrophage-induced invasive growth patterns and epithelial-mesenchymal transition of tumor cells. Validation of these results in canine mammary carcinoma tissues (n = 50) and xenograft tumors indicated the activation of non-canonical and canonical Wnt pathways in metastatic tumors and non-metastatic malignancies, respectively. Activation of non-canonical Wnt pathway correlated with number of TAMs. We demonstrated that TAMs mediate a "switch" between canonical and non-canonical Wnt signaling pathways in canine mammary tumors, leading to increased tumor invasion and metastasis. Interestingly, similar changes in neoplastic cells were observed in the presence of macrophage-conditioned medium or live macrophages. These observations indicate that rather than being "corrupted" by cancer cells, TAMs constitutively secrete canonical Wnt inhibitors that decrease tumor proliferation and development, but as a side effect, they induce the non-canonical Wnt pathway, which leads to tumor metastasis. These data challenge the conventional understanding of TAM-cancer cell interactions.